A rare trouble in the small bowel (Emergency Care Journal, 2025)
A 69-year-old woman presented to the emergency department with acute lower abdominal pain, peritonism and fever (body temperature 38.5 °C). Her past medical history was unremarkable. Laboratory tests revealed an increase of white blood cells (18.17 x 109/L; normal values 3.6-10.5 x 109/L), neutrophils (16.05 x 109/L; normal values 1.5-7.7 x 109/L), C-reactive protein (31.79 mg/dL; normal values < 0.5 mg/dL) and lactate dehydrogenase (315 U/L; normal values < 248 U/L) levels. Abdominal contrast-enhanced computed tomography (CT) scan showed a large outpouching filled by fecaloid material on the mesenteric side of a jejunal loop in the left lumbar region with stranding of adjacent fat (red arrow).
Keywords: Jejunal diverticulitis; diverticula; small bowel; abdominal pain; computed tomography; abdominal surgery